2020
DOI: 10.12659/msm.921026
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-33 Has Protective Effect Against Aβ₂₅₋₃₅-Induced Injury in SH-SH-SY5Y Cells

Abstract: Background: Alzheimer disease (AD) is a significant health issue for the elderly, and there are at present no clinically effective anti-AD agents. Prevention of Ab-induced neurotoxicity is proposed as a possible modality for treatment of AD. miR-33 has been proven to promote Ab secretion and impair Ab clearance in neural cells. The present study assessed whether miR-33 is involved in AD pathology. Material/Methods: miR-33 level was detected by qRT-PCR. The Akt/mTOR pathway was analyzed by Western blot analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Recently, the potential of blocking miR-592 in order to lower oxidative stress injury in astrocytes was reported and it was suggested to be mediated by dyslexia-associated protein KIAA0319 and (Kelch-like ECH-associating protein 1) nuclear factor erythroid 2 related factor 2-antioxidant response element (Keap1/Nrf2/ARE) signaling pathway. 179 Wang et al 180 detected upregulation of miR-33 expression in SH-SY5Y cells after treatment with Aβ 25–35 . Downregulation of miR-33 suppressed inflammation, oxidative stress, and cell apoptosis, while also improving synaptic plasticity.…”
Section: Potential Epigenetic Therapy For Admentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the potential of blocking miR-592 in order to lower oxidative stress injury in astrocytes was reported and it was suggested to be mediated by dyslexia-associated protein KIAA0319 and (Kelch-like ECH-associating protein 1) nuclear factor erythroid 2 related factor 2-antioxidant response element (Keap1/Nrf2/ARE) signaling pathway. 179 Wang et al 180 detected upregulation of miR-33 expression in SH-SY5Y cells after treatment with Aβ 25–35 . Downregulation of miR-33 suppressed inflammation, oxidative stress, and cell apoptosis, while also improving synaptic plasticity.…”
Section: Potential Epigenetic Therapy For Admentioning
confidence: 99%
“…Downregulation of miR-33 suppressed inflammation, oxidative stress, and cell apoptosis, while also improving synaptic plasticity. 180 The protective effect of miR-33 downregulation was achieved by suppressing Akt/mammalian target of rapamycin (mTOR) signaling pathway activation. 180 Intra-hippocampal injection of miR-342-3p antagomir in 3xTg-AD mice confirmed the association between miR-342-3p and AD, suggesting that miR-342-3p inhibition can improve cognitive deficits.…”
Section: Potential Epigenetic Therapy For Admentioning
confidence: 99%
See 1 more Smart Citation
“…The role of miR-33 has also been implicated in the neurodegenerative processes. Studies have demonstrated that the knockdown of miR-33 improved synaptic plasticity, reduced inflammation, oxidative stress, and cell apoptosis (Wang et al, 2020). The direct intracerebral delivery of a miR-33 antisense oligonucleotide into mouse brain was shown to be an effective strategy for increasing brain ABCA1 expression/activity, which can have beneficial effects on various neurodegenerative and cardiovascular diseases (Jan et al, 2015).…”
Section: Mir-33mentioning
confidence: 99%
“…Through targeting of multiple factors involved in GABAergic signaling, miR‐33 has been shown to directly regulate state‐dependent memory (Jovasevic et al, 2015). Additionally, multiple groups have shown that miR‐33 can promote amyloid‐beta accumulation, indicating that inhibition of miR‐33 may protect against memory loss in patients with Alzheimer’s disease (Kim et al, 2015; Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%